2021
DOI: 10.3390/ani11030790
|View full text |Cite
|
Sign up to set email alerts
|

Flaxseed Oil and Heated Flaxseed Supplements Have Different Effects on Lipid Deposition and Ileal Microbiota in Albas Cashmere Goats

Abstract: The present study investigated the effect of flaxseed grain or flaxseed oil on ileal microbiota and lipid deposition of cashmere goats. Sixty kid goats (average body weight 18.6 ± 0.1 kg) were allocated to three treatments, fed for 90 days, with control treatment: basal diet (CON, total-mixed ration), experimental treatment: basal diet with added flaxseed oil (LNO), experimental treatment: basal diet with added heated flaxseed grain (HLS). The final body weight, body weight gain, the weight of kidney fat, omen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
1
3
1
Order By: Relevance
“…It has been reported that feeding linseed oil increased the serum cholesterol concentration of cows (Oliveira et al 2021). The serum cholesterol content was increased in lambs supplemented linseed oil probably due to the stimulating https://doi.org/10.17221/77/2022-CJAS effect of fat for HDL-C, which has previously been explained in Albas Cashmere Goats (Liu et al 2021). However, in this study, no change in serum metabolites was detected in lambs fed microencapsulated linseed oil.…”
Section: Serum Biochemical Analysiscontrasting
confidence: 52%
“…It has been reported that feeding linseed oil increased the serum cholesterol concentration of cows (Oliveira et al 2021). The serum cholesterol content was increased in lambs supplemented linseed oil probably due to the stimulating https://doi.org/10.17221/77/2022-CJAS effect of fat for HDL-C, which has previously been explained in Albas Cashmere Goats (Liu et al 2021). However, in this study, no change in serum metabolites was detected in lambs fed microencapsulated linseed oil.…”
Section: Serum Biochemical Analysiscontrasting
confidence: 52%
“…Sphingosine produced by the [Eubacterium]_coprostanoligenes_group could enter the circulator stream, further regulate the host lipid homeostasis, and alleviate dyslipidemia [38]. In the present study, in the small intestine, the RA of the [Eubacterium]_coprostanoligenes_group was significantly higher in the HLS group than in the CON and LNO groups, which illustrated that flaxseed grain could increase the RA of probiotics and protect the intestinal epithelium from damage, and further absorb more c18:3n3 into the blood, thereby increasing the content of c18:3n3 in the blood [4] and alleviating the dyslipidemia [11]. The correlation analysis showed that the [Eubacterium]_coprostanoligenes_group was positive with c18:3n3, further confirming the above results.…”
Section: Discussionsupporting
confidence: 50%
“…The previous results showed that dietary supplementation with flaxseed oil or grain changed the ileal microbiota composition; flaxseed grain ameliorated the blood lipid profiles, but flaxseed oil did not. The changes in the blood lipid profiles of cashmere goats in response to dietary supplementation with flaxseed grain were probably related to the change in the ileal microbiota composition [11]. Therefore, we hypothesize that the effects of flaxseed oil or grain on the blood lipid profiles of Albas cashmere goats are related to changes in the diversity of the intestinal microbiota, and further affect host health through a variety of crosstalk mechanisms.…”
Section: Introductionmentioning
confidence: 98%
“…Meanwhile, abundance of Ruminiclostridium 9 altered when probiotic (PROB) or probiotic/prebiotic/essential oil supplement (PPEO) had been taken during a subclinical NE challenge in broiler chickens. Consistently, abundance of Intestinibacter in gut was closely related to diet such as arabinoxylan and mixed linkage glucans [30] as well as axseed oil [31]. These nutrients were generally believed to help relieve constipation.…”
Section: Discussionmentioning
confidence: 86%